Enhancing Transparency and Accountability through Citizen Feedback : Lessons from the E-ISR+ Pilot - World Bank (Washington, DC, 2013)
The External Implementation Status and Results Plus (E-ISR+) system is a feedback, transparency, and accountability tool for the World Bank. E-ISR+ is intended to disclose current project information to external stakeholders, to obtain feedback from non-state players on project progress and results, and to systematically reflect external feedback in implementation reporting. In doing so, it incorporates concepts from social accountability, third-party monitoring, and participatory monitoring and evaluation to emphasize increased transparency, accountability, and stakeholder involvement in World Bank projects. The main sections of the ISR became accessible to the public, reflecting the Bank s new access to information policies and an effort to open up more information about Bank operations to the external public. Moreover, reflecting the overall trend toward more open development, the ISR process tests a new pilot effort in several African countries. E-ISR+ is designed to contribute to an improved environment for accountability generally within the host country and particularly where civil society monitoring strengthens the ability to hold government and other institutions answerable for their expected roles in a project. An improved environment for transparency and accountability is a long-term goal; it is also dependent on variable factors.